A natural transactivation mutation in the thyroid hormone beta receptor: impaired interaction with putative transcriptional mediators - Collingwood, T N; Rajanayagam, O; Adams, M; Wagner, R; Cavaillès, V; Kalkhoven, E; Matthews, C; Nystrom, E; Stenlof, K; Lindstedt, G; Tisell, L; Fletterick, R J; et al. (Proceedings of the National Academy of Sciences - PNAS, 1997)
The syndrome of resistance to thyroid hormone is characterized by elevated serum free thyroid hormones, failure to suppress pituitary thyrotropin secretion, and variable peripheral refractoriness to hormone action. Here we describe a novel leucine to valine mutation in codon 454 (L454V) of the thyroid hormone beta receptor (TR beta) in this disorder, resulting in a mutant receptor with unusual functional properties. Although the mutant protein binds ligand comparably to wild-type receptor and forms homo- and heterodimers on direct repeat, everted repeat, or palindromic thyroid response elements, its ability to activate transcription via these elements is markedly impaired. The hydrophobic leucine residue lies within an amphipathic alpha-helix at the carboxyl terminus of TR beta and the position of the homologous residue in the crystal structure of TR alpha indicates that its side chain is solvent-exposed and might interact with other proteins. We find that two putative transcriptional mediators (RIP140 and SRC-1) exhibit hormone-dependent association with wild-type TR. In comparison, the interaction of this natural mutant (L454V) and artificial mutants (L454A, E457A) with RIP140 and SRC-1 is markedly reduced. Furthermore, coexpression of SRC-1 is able to restore the transcriptional activity of the L454V mutant receptor, indicating that the interaction of this residue with accessory proteins is critical for transcriptional activation. Finally, the occurrence of the L454V mutation in resistance to thyroid hormone, together with impaired negative regulation of the thyroid-stimulating hormone alpha promoter by this mutant, suggests that the amphipathic alpha-helix also mediates hormone-dependent transcriptional inhibition, perhaps via interaction with these or other accessory factors.